Relationship Between Nutritional Fulfillment and Wound Healing Duration in Post-Sectio Caesarea Patients at Prof. Dr. R.D. Kandou General Hospital Manado⁠ - Rizkiya Pratiwi Musa; Sulistiyah Sulistiyah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Sectio Caesarea (SC) surgery causes an incision wound in the abdomen, requiring a complex tissue healing process. Nutrition is a primary systemic factor supporting cell regeneration and new tissue formation through the intake of protein, vitamins, and minerals. However, many postpartum mothers still practice dietary restrictions due to misconceptions about the wound healing process. Objective: To determine the relationship between nutritional fulfillment and wound healing duration in post-SC patients at Prof. Dr. R.D. Kandou General Hospital, Manado. Methods:This quantitative research used an observational analytic design with a cross-sectional approach. The sample consisted of 20 postpartum mothers after SC, selected using purposive sampling technique. Research instruments included a questionnaire and an observation sheet. Data were analyzed using Fisher's Exact Test (α=0.05). Results: The majority of respondents (55%) had good nutritional fulfillment, and 60% of respondents experienced rapid wound healing. Statistical test results showed a p-value = 0.005 (p < 0.05), indicating a significant relationship between nutritional fulfillment and wound healing duration. Respondents with good nutrition had a rapid wound healing percentage of 90.9%, while respondents with poor nutrition had a slow wound healing percentage of 77.8%. Conclusion: Adequate nutritional fulfillment plays a crucial role in accelerating the wound healing process after Sectio Caesarea surgery.